Proposta de modelo baseado em competências para gerenciamento de atividades em projetos ágeis - Costa Filho, José Romualdo da (2021)
The management of activities involves the development and use of technical skills (hard skills) and interpersonal skills (soft skills). It is noteworthy that the practices, tools and skills used in the management of activities differ in relation to predictive and agile management practices. In the predictive context, the association of a development time person in an activity provided in projects is done manually and individually by the person responsible for managing the project. In agile practices, on the other hand, the management of activities takes place in an iterative and incremental process, people do not make the development time and the other stakeholders of the project actively work together to understand the problem, in addition to keeping them prioritized as activities with greater business value. In this scenario, this research aims to develop a conceptual model based on competences that help the self-assignment of quick-time activities in an iteration. To achieve this goal, this research included two phases. In the first phase, a Systematic Literature Review (RSL) was carried out to identify how studies on project management practices approach the management of activities in an iteration. In the second phase of the research, field research was carried out, where the proposed model, derived from RSL, was implemented in a computational tool, and applied in a work environment in a company that operates without a service segment, with the development of its products using agile project management practices. The results contributed to reduce the problems related to measurement and self-designation of activities in associations under agile project management practices. The contribution of this dissertation is to offer a computational tool, as an aid tool in the process of self-assignment of activities of agile time in an iteration, since research carried out in the academic database does not have computational models compatible with the computational model presented. in this research. The research limitations for addressing only the Scrum and Kanban agile frameworks and limited to two-stage development activities. Future studies can be carried out to analyze the use of the computational tool in associations with agile practices at scale or with longer development times. This study is part of the PPGP-UNINOVE Project Management research line, in the context of the research project on Agile and Hybrid Projects and the project financed by the CNPq Universal Notice. From this study, a software registry and a utility model were produced.